Social work and restorative justice skills for dialogue, peacemaking, and reconciliation - Beck, Elizabeth; Kropf, Nancy P.; Leonard, Pamela Blume (New York ; Oxford : Oxford University Press, 2011)
Restorative justice and social work share a number of principles and goals, as they both seek to stem violence and to address the pain associated with harm. This work examines the ways that these two disciplines intersect.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Restorative justice; Social service; Social work with criminals; Victims of crimes -- Services for